Mechanical properties and deformation behavior of a high entropy alloy with precipitate under cycle loading - Song, Junhan; Zhang, Jie; Peng, Jing; Song, Xinhua; Liang, Long; Feng, Hui (Frontiers in Materials, 2024)
Compared to the traditional alloys, high entropy alloys (HEAs) exhibit exceptional strength and outstanding ductility, making them highly attractive for use in demanding engineering applications.However, the atomic-scale deformation behavior of HEAs with precipitate under the low-cycle loading conditions has not been well studied. Here, we utilize molecular dynamics simulations to investigate the low cycle fatigue behavior of AlCoCrFeNi HEAs with AlNi-rich phase, in order to better understand the cyclic deformation, work hardening, and damage mechanisms. In the stress-strain hysteresis loops, the stress in the elastic stage exhibits a gradual linear increase, followed by fluctuations at yielding and plastic deformation. The strain hardening depends on the cycle number after the yielding stage. With an increase in the number of cycles, the activation mode of stacking faults gradually transitions from a multi-slip system to a single-slip system, attributed to the gradual phase transformation. A thorough examination of dislocation evolution is crucial in understanding the strengthening and plastic behavior of materials under cyclic loading. The generation of more stair-rod dislocations further suppresses the movement of dislocations. The combined effects of element diffusion, structural transformation, and incoherent precipitation play a critical role in enhancing the mechanical properties of AlCoCrFeNi HEAs. The strength of HEA is improved through interface strengthening caused by element diffusion and structural transformation, along with dispersion induced by incoherent precipitation. This work provides a detailed atomic-level understanding of the cyclic deformation-induced strengthening mechanism, in order to design high-strength and ductile HEAs with specific desired properties.